Studi Pertumbuhan Rumput Mulato pada Bulan Pertama Pasca Pemberian Pupuk Kandang Berbeda - Muh. Irwan; R Rasbawati; Reza Asra; Fitriana Akhsan (JURNAL GALUNG TROPIKA, 2020)
Ruminant livestock development is largely determined by the carrying capacity of feed sources because the availability of quality feed is a major factor of success. The quality of natural grass that has been relied on so far must be improved by utilizing superior grass which produces better biomass and nutrients. Mulato grass (Brachiaria hybrid cv. Mulato) is one of the superior grasses that has not been widely cultivated in South Sulawesi. This study aims to look at the growth of mulato grass fertilized with different types of manure. The research design applied was a completely randomized design (CRD) with 4 treatments of giving fertilizers and 3 consecutive repetitions consisting of no treatment, administration of goat feces, treatment of cow feces, and treatment of layer chicken feces. The variables observed were plant height, plant length, number of tillers, and number of leaves which were carried out every week after being uniform. The results showed that the use of cow feces gave the best results on all variables measured in details of the best plant height 44.2 cm, plant length 68.3 cm, 70 pieces, and 11.3 tillers.